Reliability, availability and maintainability study for failure analysis in series capacitor bank. (April 2018) - Arias Velásquez, Ricardo Manuel; Mejía Lara, Jennifer Vanessa
Abstract: In this research, the objective is introducing the fundamentals of reliability analysis, it has been applied to the planning and design of Series Capacitor (SC) Bank, applied for power lines. It considers the cost of power outages, the decision process for new and existing power equipment in several systems, as well as the ability to make quantitative analysis "Cost – Vs. - Reliability" trade-off studies. The lack of credible data concerning equipment reliability and the cost of power outages has hindered engineers in making such studies. The study case considers a Reliability, Availability, and Maintainability (RAM) calculations, it has been performed for the series capacitor banks to be located at Cotaruse 220 kV, 4500 m over sea level (mosl) in a substation, located in Peru. The calculations are divided into forced and scheduled outages. A crew delay (for example: travel time) of 2 h, as well as 1 h for switching, have been included in calculations. The results are divided into forced and scheduled outages with a reliability calculation and spare parts are listed in this research. Highlights: To introduce the reliability analysis applied to the planning and design of Series Capacitor. A case study considers a Reliability, Availability, and Maintainability for 220 kV substation. The results propose the outages analysis with a reliability design and spare parts proposal.